Motivating factors of innovative research activities and barriers to R&D in Kazakhstan - Ilmaliyev, Zhanserik B.; Patihan, Talafuhan; Tursunbekov, Daniyar M.; Kenzhaliyev, Olzhas B.; Sansyzbayeva, Dinara B.; Kassymova, Gulzhaina K. (Jurnal Cakrawala Pendidikan, 2022)
While higher education, science, and industry have become key factors in the national and economic growth of a country, they perhaps act as independent performers. This paper aims to describe the development of innovative commercialization activities based on the dissemination of innovations in the fields of research, education, and business. The present research, using empirical studies as its research method, first reviewed the current worldwide status of research studies to see their contribution to knowledge transfer. Second, it portrayed the results of an online survey of 100 respondents studying and teaching or researching at Kazakhstani universities to better understand the innovative research activities and motivations of and barriers to the research and development (R&D) in the Republic of Kazakhstan. The results of the proposed approach are presented in the case of Kazakhstani researchers. Based on such findings, some recommendations are made for better Kazakhstani education, industry, and science alignment so that research in this country can have a greater impact on economic growth.